Model Keputusan Penentuan Jenis Distribusi Dari Kerusakan Bearing Pada Mesin TFO Di PT XYZ - Tombak Gapura Bhagya; Graha Prakarsa (Universitas Informatika dan Bisnis Indonesia, 2020)
Companies at this time are required to be able to make the machine work as optimal as possible. But engine performance will not be optimal if the maintenance of the production machine is not properly regulated. One way to do maintenance is to know the pattern of damage to parts of the machine. Bearing on TFO machines is a part that is quite widely used, on one machine can use up to 512 bearings. And if it is damaged, the machine must stop operating for up to 3 days, but if the pattern of bearing damage can be found, the bearing replacement process will only take 4 hours. Based on the data obtained, the bearing crushing rate on the TFO machine at PT XYZ is Weibull distribution, this can be seen from the index of fit value which is greater than the other distributions.